2007
DOI: 10.1007/s12011-007-8035-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Minerals in Obesity-related Diseases in the Chandigarh (India) Population

Abstract: Excessive Zn but normal Cu and Mg in the staple food consumed by the people of Chandigarh (Union territory and capital of Punjab and Haryana States of India) has been considered to be the major risk factor for the prevalence of obesity (33.15%) and obesity-related diseases in this region. Therefore, in the present investigations, in obesity-related diseases, the status of these minerals was estimated in their tissues, including hair, nails, and blood serum and urine, and compared with those of normal subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
0
6
0
1
Order By: Relevance
“…Yakinici et al [44] reported that copper concentration was significantly higher in the obesity group than in the normal group, whereas other studies reported no difference between two groups [45,46]. Furthermore, copper concentration in diabetes patients was found to be lower than that of normal group [47]. In most mammalian species, insulin is stored in the pancreatic β cells as Zn crystals [48].…”
Section: Discussionmentioning
confidence: 99%
“…Yakinici et al [44] reported that copper concentration was significantly higher in the obesity group than in the normal group, whereas other studies reported no difference between two groups [45,46]. Furthermore, copper concentration in diabetes patients was found to be lower than that of normal group [47]. In most mammalian species, insulin is stored in the pancreatic β cells as Zn crystals [48].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, there are increasing evidences that excessive Zn in diet induces obesity, diabetes, dyslipidemia and hypertension in experimental animals [10]. Higher concentration of Zn and lower concentration of Cu, Mg and Mn in the tissues of human and some populations have been reported to link the ionic imbalance of nutritionally important elements to the etiology of diseases [11]. Moreover, excessive Zn intake by supplementation can impair immunologic function, interfere with metabolism of other essential minerals and other lipid indices [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also showed that the status of minerals in the obesity-related diseases depend on the choice of the food consumed to improve the quality of life and prognosis of the diseases [25].…”
Section: Discussionmentioning
confidence: 99%